POCIS sampling in combination with ELISA: screening of sulfonamide residues in surface and waste waters - Černoch, Ivo; Fránek, Milan; Diblíková, Iva; Hilscherová, Klára; Randák, Tomáš; Ocelka, Tomáš; Bláha, Luděk (Journal of environmental monitoring, 2012)
Sulfonamide antibiotics coming from both human and veterinary medicine are among the most common emerging pollutants in freshwater. The present paper shows the successful application of passive sampling using POCIS in combination with an immunochemical ELISA technique and HPLC/MS/MS analysis to study the distribution of sulfonamides in streams around small towns in the Czech Republic, as well as around a major agglomeration of the city of Brno, including its waste water treatment plant (WWTP). Results indicated the presence of sulfonamides at most studied sites with concentrations ranging from <20 up to 736 ng of sulfamethoxazole equivalents per POCIS. Very high levels were detected in both the influent and effluent of the Brno WWTP with maxima > 8000 ng SMX per POCIS. All samplers collected down-stream of the studied towns and WWTPs clearly showed an increase in sulfonamide drug residues. Higher concentrations were determined in rivers at the city of Brno agglomeration. In agreement with other available studies, these findings indicate low efficiency of conventional WWTPs to eliminate polar pharmaceuticals such as sulfonamides. Good performance and correlation with the LC/MS results, as well as ease of use, indicate good potential for the immunochemical ELISA technique to become the screening tool for sulfonamide determination in surface waters including passive samplers.
Keywords: Water Pollutants, Chemical; Enzyme-Linked Immunosorbent Assay; antibakteriální látky; Czech Republic; Anti-Bacterial Agents; sulfonamidy; Environmental Monitoring; chemické látky znečišťující vodu; ELISA; Water Pollution, Chemical; Waste Disposal, Fluid; Sulfonamides; Česká republika; chemické znečištění vody; monitorování životního prostředí; odpad tekutý - odstraňování